INSTITUTIONAL RACISM IN SULTANZADAH'S NOVEL 'SHAM-E AKHIR-E AFGHANI' (2021): - Mohammadi, Noria (UIN Raden Mas Said Surakarta, 2024)
This research addresses institutional racism in Afghanistan, focusing on Mohammad Asif Sultanzadah's novel entitled Sham-e Akhir-e Afghani (2021). Utilizing the theoretical framework of institutional racism from Carmichael and Hamilton (1967), this study employs a qualitative approach with textual analysis as the primary tool. In the novel, Sultanzadah’s narrative highlights institutional racism perpetrated by extremist Pashtuns (Taliban) and Afghan government against Hazaras. Findings indicate that racism persists in Afghan society, with Hazaras that differ in ethnicity, religion, and culture, experiencing significant discrimination, particularly in various social settings. While Pashtuns are seen as a superior democratic power condemning individual racism, Hazaras face systemic racial discrimination in education, relationships, housing, and the economic system. This study underscores the urgent need to address institutional racism in Afghanistan.